Application of Treatment for Deep Hole Drilling Debris in Gas-Rich Soft Coal Seams. (19th April 2023) - Niu, Yihui; Xu, Zuoming; Wang, Wenhe; Jing, Xiaofei; Mi, Hongfu; Zhong, Zhen
Abstract : Hole accidents occurring in the drilling process and borehole collapse encountered in gas production are obstacles standing in the way of high efficiency of gas drainage through the outburst-prone soft coal seams in China. The fundamental testing data from existing suspending agents were combined to prepare a suspension in a specific density for testing debris disposal technology considering several adverse effects. Those effects include the sizeable residual volume of drilling debris, difficult debris disposal, the low effective utilization rate of drill holes, and the unideal extraction effect in drill holes with long-distance downward drill holes. The testing outcomes indicated that the suspension-aided debris disposal could contribute to the following aspects: discharging residual drilling debris out of the drill hole, rinsing the drill hole, preventing drilling debris from filling the coal seam, providing the adequate drill hole depth, and improving the effects of gas extraction. As a result, the gas production in shallow drill holes was increased by 40%, with gas concentration elevated by 21%. In addition, the scalar quantity and extraction concentration in the gas concentration of deep drill holes were increased by 84% and 260%, respectively. This study was undertaken to provide a specific reference for debris disposal work of deep drill holes for gas-rich soft coal seams.